Application of problem based learning to improve lower passing volleyball for 5th grade students - Mohammad Nur Fahmi Setyo Aji; Raymond Ivano Avandi; Mokhamad Fuad Nudyanda; Muhammad Alfan Asyhari; Muhammad Brillian Rifti Aditia; Muhammad Fafi Nu’amil Aufa; Setyawan, Risfandi (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
The failure of volleyball psychomotor learning outcomes is because not all children can perform the basic movements of lower passing properly. The objective of this research is to measure the psychomotor learning outcomes of lower passing by applying problem-based learning as a learning model. The design of classroom action research with a two-cycle diagram was applied involving 29 children (Male=14, Female=15, Mage=11,034) as the sample of this research. Percentage calculation and descriptive statistics are the analysis techniques determined with the help of Microsoft Excel to review the proportion of completeted and non completed of psychomotor learning outcomes. The results of the study showed an increase in the average value from cycle I of 70.93 to 77.51 in cycle II. Meanwhile, the results of the frequency distribution of completeness also increased from cycle I of 65.50% (19 students) to 82.20% (24 students) in cycle II. The results in this study have contributed to affirming PBL as a model worthy of being used as an alternative learning strategy for volleyball lower passing, especially in the psychomotor domain. Self-confidence, motivation level, and learning burnout experienced by students are observational notes of obstacles that are not considered as objective measures in this study. Future researchers need to take into account these predictor variables in depth through multivariate analysis